Understanding computers today and tomorrow : comprehensive - Morley, Deborah; Parker, Charles S. 1945- (Cengage Learning, 2015)
Gives your students an introduction to computer concepts with a modern twist. Known for its emphasis on industry insight and societal issues, this text makes concepts relevant to today's career-focused students.